Unpacking Hidden Learning Networks Among Adolescents in Community-Driven Educational Spaces - Sodikin Sodikin; Khermarinah Khermarinah; Antaris Fahrisani; Aliah Bagus Purwakania Hasan (Asian Journal of Applied Education (AJAE), 2026)
Informal learning in community-based education spaces plays a vital role in adolescent development, yet the structure of learning networks within these spaces is often overlooked. This qualitative case study explores learning networks and community dynamics shaping adolescent learning experiences in a community education space in South Tangerang City. Data from interviews, observations, and document analysis reveal that learning occurs through organically formed social networks characterized by key connecting actors, interest-based collaboration, and spontaneous knowledge sharing. Community spaces function as supportive ecosystems that strengthen adolescent agency, creativity, and social capital, complementing formal education and contributing to more adaptive and inclusive non-formal education models.